1980
DOI: 10.1016/0378-5963(80)90070-7
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of oxygen with Ni(100) and the reduction of the surface oxide by hydrogen

Abstract: The interaction of oxygen with Ni(100) has been studied with ellipsometry, Auger electron spectroscopy and low energy electron diffraction. The observations of other workers are completely confirmed. The same techniques and procedures have been used to study the reduction of the surface oxide with hydrogen. It is found that the reduction reaction requires hydrogen atoms, adsorbed on exposed nickel atoms. At temperatures between 150 and 250°C and hydrogen pressures up to i0~5Torr, the reduction proceeds via a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…Thus, it was concluded that the probability for the reaction dissociation of the adsorbate. The similar result was obtained in [30] by a quantum chemical calculation, confirming that H 2 can be only dissociatively adsorbed on lattice defects on NiO x . In the result of hydrogen dissociation, the last one migrates to the SnO 2 surface and interacting with chemisorbed oxygen gives contribution to the change of the free electron concentration change in nanowire, stipulating further gas sensitivity growth.…”
Section: ) Ni Atoms Interaction With Sno 2 Nw Matrix and Their Incorsupporting
confidence: 75%
“…Thus, it was concluded that the probability for the reaction dissociation of the adsorbate. The similar result was obtained in [30] by a quantum chemical calculation, confirming that H 2 can be only dissociatively adsorbed on lattice defects on NiO x . In the result of hydrogen dissociation, the last one migrates to the SnO 2 surface and interacting with chemisorbed oxygen gives contribution to the change of the free electron concentration change in nanowire, stipulating further gas sensitivity growth.…”
Section: ) Ni Atoms Interaction With Sno 2 Nw Matrix and Their Incorsupporting
confidence: 75%
“…In contrast to Ni(lOO) [15] there was no unequivocal relationship between SA and the AES oxygen peak height (cf. fig.…”
Section: Oxidationmentioning
confidence: 99%
“…The base pressure was about lo--" Torr. The crystal was the same as the one used in previous experiments [37,38]. Ellipsometry was done at an angle of incidence of 68.2" and at a wavelength of 6328 A with either two-zone or off-null irradiance measurements.…”
Section: Methodsmentioning
confidence: 99%